Forty Years of the Collected Works of Erasmus - Crane, Mark (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
This article discusses the origins and development of the Collected Works of Erasmus series, a project to translate the vast majority of the Dutch humanist Erasmus of Rotterdam’s Greek and Latin writings into English. A unique partnership between the University of Toronto Press and a team of Canadian and international scholars, the series is roughly 70 percent complete. Sixty of the projected eighty-six volumes have been published. Conceived by the late Ron Schoeffel, a long-serving editor at the Press, the series is expected to be complete by 2030.